MEDIA SOSIAL INSTAGRAM SEBAGAI PRESENTASI DIRI MAHASISWI PENDIDIKAN SOSIOLOGI UNTIRTA - Rizki Setiawan; Nurul Audie (Jurnal Community, 2020)
This study aims to find out how Untirta Sociology Education students present themselves on Instagram, why Untirta Sociology Education students choose Instagram social media to present themselves compared to other social media. This study uses qualitative research with descriptive research methods, and data collection techniques through interviews in depth with interviewees. The theory used in this study is the Dramaturgy Theory by Erving Goffman. Informants in this study were two active users of Instagram in Untirta's Sociology Education. The results of this study are Untirta Sociology Education students using filters, feeds, uploading photos or videos, and uploading Instastory to present themselves well on Instagram.